Real space study of local bonding for zinc structure based on temperature-dependent x-ray pair distribution function analysis - Ahmad S. Masadeh; Moneeb T. M. Shatnawi; Ziad Y. Abu Waar; Gassem M. Alzoubi; Yang Ren (AIP Advances, 2022)
Zinc metal has a hexagonal close packing hcp structure with an unusual axial ratio c/a. This work presents the local atomic structure analysis of elemental zinc using the x-ray atomic pair distribution function (PDF) method and total synchrotron x-ray scattering in the temperature range of 100–300 K. In this PDF study, we determined the evolution of local bonding in zinc structure in the temperature range of 100–300 K by fitting the first two peaks in the radial distribution function (RDF), R(r), with two Gaussian peaks. Our local structure results reveal a piece of evidence for unusual bond length behavior at low temperatures. The PDF analysis revealed that the a-axis varies linearly from 300 to 160 K and remains constant below 160 K. This local structural result indicates that at temperatures below 160 K, the Zn–Zn bonds are no longer thermally contractible in the ab plane, in agreement with standard crystallographic analysis [J. Nuss et al., Z. Anorg. Allg. Chem. 636, 309 (2010)]. Another significant observation is that the local thermal expansion for the a-axis was found to be three times larger than the one obtained using conventional crystallographic methods [U. Wedig et al., Z. Anorg. Allg. Chem. 639, 2036 (2013)]. This PDF result shows the advantage of total scattering PDF methods in studying the local structural features in elemental zinc, which cannot be captured by the crystallographic model. In addition, this PDF study demonstrates that multiple RDF-peak fitting is a useful approach for interpreting the local structural features of such a non-ideal hcp structure.